Identity and Buddhism in Can Xue's Frontier. Issue 1 (1st January 2021) - Rothfork, John
ABSTRACT: Can Xue's Chinese novel, Frontier, seems to have little coherence. It is often thought to offer a pastiche of dream images. However, an understanding of Zen Buddhism, provided by T. P. Kasulis' Zen Action Zen Person, offers a vocabulary to explain how the characters in the novel seek answers to koans as they struggle to find meaning in their dreams, perceptions, and meditation. Liujin, the main character, doesn't find Western philosophic answers, but is described in the end as giving up thinking, the goal in Zen Buddhism and in Taoism (cf. wu-wei ) to enjoy "the touch of the cool evening air." Like Kasulis' enlightened monk, Liujin sits to sit (in zazen or meditation), rather than sitting in hopes of enlightenment. She sits to have being, to taste being ( rasa ). "Bit by bit, her mind became luminous."